Nutrient and bioactive analyses of forests foods for policy making on food and nutrition security in Central Africa - Fungo, R.; Tieguhong, J.C. (Juniper Publishers, 2019)
A serious public health challenge may be envisaged in central Africa, especially with a growing population, rapid westernization of traditional African diets and increasing demand for sufficient essential nutrients and bioactive compounds. However, having the second largest tropical rainforest basin in the world, forest foods that are widely consumed in Central Africa contain adequate essential nutrients such as carotenoids, flavonoids, proanthocyanins, polyphenols, vitamins C and E, Fe, Se, Ca and Na. This review purports that forest foods can considerably contribute towards meeting human nutrient requirements by replacing imported western foods that are generally more expensive and lower in essential nutrients. We recommend that forest foods should be considered in setting nutrition education strategies and formulating policies governing food and nutrition security in Central Africa.